Speed Control of Switched Reluctance Motor Drive Based on PID Controller - Hairik, Haroutuon A.; Thejel, Rabee’ H.; Hameed, Samar (Basrah Journal for Engineering Sciences, 2015)
This study presents a speed control design for switched reluctance motor (SRM) drive based on PID controller. The applications of Switched Reluctance Motors (SRMs) have being increased day by day, but this type of motors represents a highly nonlinear system, therefore there are a lot of difficulties in modeling and controlling them. We have proposed a non-linear mathematical model of a four phases 8/6 poles SRM then simulated it through Simulink/Matlab facilities. The whole control mechanism consists of a hysteresis current controller to minimize the torque ripple and a PID speed controller. The control design results are then validated in real-time by Simulink/Matlab software package.